Sentra Produksi Tenun Songket Dan Batik Tabir Di Pekanbaru Dengan Pendekatan Arsitektur Neo Vernakular - Nabila Shalihah; Pedia Aldy; Yohannes Firzal (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Tenun Songket and Batik Tabir are Riau typical handicrafts. The demand for these fabrics has increased because of the large public interest in using these fabrics in various events. However, the market demand cannot be fulfilled because the numbers of production and craftsmen from Tenun Songket and Batik Tabir are still low. As a result of these factors, a production center is needed that can overshadow the production process of Songket and Batik Tabir. This production center aims to accommodate the creativity of Songket and Batik Tabirs’ craftsmen from regencies in Riau that produce high-quality Tenun Songket and Batik Tabir.The production centers also facilitate promotional activities and education for the community. Not only accommodates production activities, so that traditional handicrafts from Tenun Songket and Batik Tabir can develop well and become an identity for the people and culture of Riau. The Production Center is designed through the Neo Vernacular Architecture approach that mimics some or several elements of the physical form of the building or non-physical elements of the building in the form of layout, mindset and culture. The selection of this theme is considered appropriate for more modern Production center of Tenun Songket and Batik Tabir.Keywords: Tenun Songket, Batik Tabir, Production Center, Neo Vernacular Architecture